2001
DOI: 10.1074/jbc.m108231200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Novel Multidrug Transporters from Human Pathogens

Abstract: Proteins of the Smr family are the smallest multidrug transporters, about 110 amino acids long, that extrude various drugs in exchange with protons, thereby rendering bacteria resistant to these compounds. One of these proteins, EmrE, is an Escherichia coli protein, which has been cloned based on its ability to confer resistance to ethidium and methyl viologen and which has been extensively characterized. More than 60 genes coding for Smr proteins have been identified in several bacteria based on amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 27 publications
5
67
0
Order By: Relevance
“…EmrE, Hsmr, BPsmr, PAsmr, and TBsmr) and heterodimers (e.g. EbrAB) have been identified (26,27,32,33). Membrane protein topology is largely governed by the positive-inside rule, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EmrE, Hsmr, BPsmr, PAsmr, and TBsmr) and heterodimers (e.g. EbrAB) have been identified (26,27,32,33). Membrane protein topology is largely governed by the positive-inside rule, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction with EmrE is a nonproductive one that may result in the formation of a heterodimer with low or no activity. We have previously shown that EmrE can interact with a variety of homologues forming heterodimers with various affinities (32).…”
Section: Discussionmentioning
confidence: 99%
“…The Glu14 residue is conserved in the SMR family multidrug transporters. 22) It has been reported with EmrE of E. coli that Glu14 is involved in the binding of substrate. 23) Thus, it is likely that Glu14 in the SsmE is also involved in substrate binding.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and biochemical evidence suggests that the basic EmrE oligomer is a dimer (7)(8)(9)(10). EmrE has only one membraneembedded charged residue, Glu14, that is conserved in more than 100 homologous proteins (5,11) and plays a central role in substrate and proton binding (12)(13)(14)(15). Deprotonation of Glu14 is required for substrate binding (4,14).…”
mentioning
confidence: 99%
“…It is a small (110-residue) multidrug transporter that extrudes various positively charged drugs in exchange for protons, thus rendering bacteria resistant to these drugs (1)(2)(3). The protein has been characterized, purified, and reconstituted in a functional form (1,(4)(5)(6). High-affinity substrate binding has been established as a reliable and sensitive assay for activity of the detergent-solubilized transporter (4).…”
mentioning
confidence: 99%